Identification of Active Compounds from Sambung Nyawa Leaves (Gynura procumbens (Lour.) Merr) as Potential Natural Antioxidant and Anti-inflammatory Agents - Saristiana, Yuneka; Salmasfattah, Novyananda; Prasetyawan, Fendy; Savitri, Lisa; Kadir, Mujtahid Bin Abd (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2025)
Diseases caused by oxidative stress and inflammation are global health problems that encourage the search for alternative treatments from natural materials. Grapevine leaves (Gynura procumbens (Lour.) Merr.) have long been empirically used, but scientific validation of their potential is still limited. The objective of this research is to identify and describe the active substances in sambung nyawa leaves and assess their effectiveness as natural antioxidants and anti-inflammatory agents. The study involves conducting laboratory experiments, starting with the extraction of sambung nyawa leaves using 96% ethanol solvent through a maceration process. The extract obtained is then analysed for its phytochemical composition. The antioxidant activity is evaluated using the DPPH method to determine the IC₅₀ value. On the other hand, the anti-inflammatory properties are tested in male Wistar rats following the induction of rat hind paw edema with 1% carrageenan, using extract doses of 75, 150, and 300 mg/kgBW. The findings indicate a 13.4% yield from the extraction process. The phytochemical analysis reveals the presence of flavonoids, alkaloids, saponins, tannins, phenols, and steroids/triterpenoids. The antioxidant test results show a moderate level of activity with an IC₅₀ value of 89.26 µg/mL. In the anti-inflammatory test, the 150 mg/kgBW dose demonstrates the highest efficacy with a 52.00% reduction in edema, comparable to the positive control triamcinolone (55.00%). In summary, the ethanol extract of sambung nyawa leaves exhibits promising potential as an antioxidant and anti-inflammatory agent, indicating its suitability for further development as a botanical pharmaceutical ingredient.